2006
DOI: 10.1007/s00011-006-6001-6
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumor necrosis factor α F(ab')2 antibody fragments protect in murine polymicrobial sepsis: Concentration and early intervention are fundamental to the outcome

Abstract: These results suggest that in processes where excessive production of cytokines is involved, the aim should be to return them to their physiologically acting range but not to inhibit their production. The timing of initiating therapy should also be considered in order to maximize the possible benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 51 publications
3
7
0
Order By: Relevance
“…Consistent with our previous findings [10,26], TNF levels were found not to be elevated. This is not an odd result, since other groups have described the same phenomenon.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Consistent with our previous findings [10,26], TNF levels were found not to be elevated. This is not an odd result, since other groups have described the same phenomenon.…”
Section: Discussionsupporting
confidence: 82%
“…This could be explained by an excessive proinflammatory cytokine blockade by the higher doses, which in turn results in immunosuppression or even in enhancement of the anti-inflammatory cytokine network, similar to that seen in CARS; this suggests that the use of high doses of anti-cytokines to completely deplete circulating cytokines seems not to be the best strategy in the treatment of sepsis. In confirmation, we have reported that the administration of anti-TNF F(ab 0 ) 2 fragments at 10 mg/kg does not decrease mortality in murine CLP-induced sepsis; however, when it is used at doses of 1 mg/kg a significant decline in mortality is achieved [10].…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Excessive production of these cytokines can result in dramatic pathologic sequelae, including a systemic capillary leak syndrome, tissue injury, shock, and fatal organ failure (6 -15). Evidence in mice, using the cecal ligation and puncture (CLP) 4 model, suggests that neutralization of TNF-␣ or IL-1␤ as a therapeutic approach was either ineffective (16,17) or, in one study, provided a modest benefit that was strain dependent, very sensitive to changes in dose, and effective only when given before CLP (18). In human sepsis, the anticytokine approach also has been ineffective (19 -21) or, in some instances, may have provided a slight, usually statistically insignificant, beneficial effect (22)(23)(24).…”
mentioning
confidence: 99%